2014
DOI: 10.3122/jabfm.2014.03.130016
|View full text |Cite
|
Sign up to set email alerts
|

Community Size and Organization of Practice Predict Family Physician Recertification Success

Abstract: Objective: Health disparities exist between rural and urban areas. Rural physicians may lack sufficient medical knowledge, which may lead to poor quality of care. Therefore, we sought to determine whether medical knowledge differed between family physicians (FPs) practicing in rural areas compared with those practicing in metropolitan areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
(9 reference statements)
0
10
0
Order By: Relevance
“…5 Specifically, we found that physicians in urban areas scored 15.6 points lower than rural physicians on the examination and were 27% less likely to pass the examination (OR ϭ 0.73; 95% CI, 0.62-0.87). When the SP4PC scale was added to the regression models, the relationship between urban location and examination score was reduced 66% to 5.8 points but was still statistically significant.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…5 Specifically, we found that physicians in urban areas scored 15.6 points lower than rural physicians on the examination and were 27% less likely to pass the examination (OR ϭ 0.73; 95% CI, 0.62-0.87). When the SP4PC scale was added to the regression models, the relationship between urban location and examination score was reduced 66% to 5.8 points but was still statistically significant.…”
Section: Resultsmentioning
confidence: 90%
“…4 Previous research found that self-designated community size, used as a rural/urban proxy, was associated with passing the American Board of Family Medicine (ABFM) Maintenance of Certification for Family Physicians (MC-FP) examination. 5 Specifically, family physicians located in metropolitan communities (Ͼ 500,000 residents) were 33% less likely to pass the MC-FP examination compared with family physicians in rural (Ͻ 25,000 residents) communities. The ABFM MC-FP examination content is based on a blueprint that mirrors the breadth and scope of family medicine training; 6 as such, it stands to reason that physicians who maintain a broader scope of practice may be more likely to pass the MC-FP examination than physicians with a narrower scope of practice.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These studies found that group rather than solo practice is associated with better performance on MOC exams. [66][67][68] Evidence regarding the association between age and MOC exam performance was mixed. Among internists, surgeons, and anesthesiologists, taking an MOC exam for the first time at a younger age was associated with higher exam scores.…”
Section: Characteristics and Activities Associated With Moc Exam (Parmentioning
confidence: 99%
“…73,74 Better scores on initial certifying exams were associated with better MOC exam scores for internists, surgeons, and anesthesiologists. 66,69 Other characteristics associated with MOC exam performance were U.S. medical training for internists and surgeons; 66,75 rural practice location or broader scope of practice for family physicians; 68,76 and for anesthesiologists, the male sex, a lack of disciplinary action, and taking the exam earlier in cycle. 69 A survey of emergency medicine physicians found that the vast majority of participants identified a benefit to preparing for the exam (e.g., increasing or reinforcing knowledge); in addition, identification of knowledge reinforcement as a benefit of the exam was associated with a small but significant difference in exam performance.…”
Section: Characteristics and Activities Associated With Moc Exam (Parmentioning
confidence: 99%